2021
DOI: 10.1111/1475-6773.13855
|View full text |Cite
|
Sign up to set email alerts
|

Postacute care outcomes in home health or skilled nursing facilities in patients with a diagnosis of dementia

Abstract: Objective: To compare the outcomes of postacute care between home health (HH) and skilled nursing facilities (SNFs) following hospitalization among Medicare beneficiaries with a diagnosis of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Furthermore, our model does not account for a growing emphasis on PAC which can be delivered in a home-based setting. (25,26) Finally, our model is parsimonious and does not include alternative variables that could predict discharge destination (e.g., social determinants of health).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our model does not account for a growing emphasis on PAC which can be delivered in a home-based setting. (25,26) Finally, our model is parsimonious and does not include alternative variables that could predict discharge destination (e.g., social determinants of health).…”
Section: Discussionmentioning
confidence: 99%
“…Given the imbalanced ratio of discharges to PAC relative to discharges to home, a random undersampling approach was applied to the derivation cohort for developing the best t model without introducing bias into the covariates' parameter estimates. 25,26 The parameter estimates, odds ratios, and their con dence intervals of covariates are unaffected by the strati ed sampling methods, while the intercept parameter estimate is the only part in the model that is affected by the resampling.…”
Section: Discussionmentioning
confidence: 99%
“…Following prior studies, PAC transitions were identified for each index hospitalization using hospital discharge status code from MedPAR. 2,12 Our focus was on transitions to SNF (including inpatient rehabilitation facilities) and home with and without HHC.…”
Section: Post-acute Care Transitionmentioning
confidence: 99%
“…Care transitions among older adults with ADRD are of particular interest because some care settings, such as SNF, are higher-cost, but may not necessarily produce better outcomes. In fact, Burke et al, 12 have suggested similar 30-day readmission and mortality outcomes for dementia patients who transitioned to HHC or SNF. Persons with dementia may be particularly at risk of experiencing preventable or unnecessary care transitions, 13 which may be further exacerbated among racial and ethnic minorities.…”
Section: Introductionmentioning
confidence: 96%
“…In 2020, about 3.1 million homebound Medicare beneficiaries received HHC, which provides skilled nursing, therapy, social work, and aide services. 1 Although the HHC setting is focused on rehabilitative goals of care, 1,2 the acuity of HHC patients has increased markedly in recent years. 1 Indeed, growing evidence shows that HHC patients experience burdensome transitions, even at the end-of-life (EoL).…”
Section: Introductionmentioning
confidence: 99%